2011
DOI: 10.1001/archsurg.2011.244
|View full text |Cite
|
Sign up to set email alerts
|

Halo Effect for Bariatric Surgery

Abstract: Bariatric surgery is an effective treatment for morbid obesity, which is increasingly recognized as a familial disease. Healthy behavior transmission may be enhanced by family relationships.Objective: To determine changes in weight and healthy behavior in patients who underwent Roux-en-Y gastric bypass surgery and their family members.Design: Prospective, longitudinal, and multidimensional health assessment before and 1 year after index Roux-en-Y gastric bypass surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 27 publications
(23 reference statements)
1
32
0
Order By: Relevance
“…While patients had more body fat than family members, most patients were women, who typically have more body fat than men. Several studies [8, 9, 25, 39, 40] also evaluated the weight of patients’ family members and similarly found high rates of obesity. Collectively, our findings indicate that bariatric surgery patients’ family members also live with overweight and obesity, and in our study, many lived with obesity-related comorbidities.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…While patients had more body fat than family members, most patients were women, who typically have more body fat than men. Several studies [8, 9, 25, 39, 40] also evaluated the weight of patients’ family members and similarly found high rates of obesity. Collectively, our findings indicate that bariatric surgery patients’ family members also live with overweight and obesity, and in our study, many lived with obesity-related comorbidities.…”
Section: Resultsmentioning
confidence: 99%
“…Future studies could follow patients over time to evaluate the impact of social support and familial dietary and activity patterns on weight loss, as well as changes in social support and familial health behaviors. To date, three studies [8, 9, 40] have examined changes in weight in spouses of bariatric surgery patients, with mixed results. Two studies [9, 39] found that obese spouses experienced reductions in weight, while a third [40] found that many obese spouses gained weight and postulated that spouses may consume the patients’ leftover food.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although weight loss surgery has shown good results, it is not a “quick fix”; it requires lifestyle modifications, so persistent weight loss and health effects can be fully appreciated (Vidot et al, 2015). Lifestyle modifications can affect both the individual and his/her family (Bylund et al, 2013; Willmer et al, 2015; Woodard, Encarnacion, Peraza, Hernadez-Boussard, & Morton, 2011) when they are faced with a new situation, as a result of GBP (Sogg & Gorman, 2008). However, research on how families handle lifestyle modification and associated physical and psychosocial changes is scarce (Grimaldi, 2010; Vidot et al, 2015).…”
Section: Introductionmentioning
confidence: 99%